Indigenous Forest Conservation Model Based Local Wisdom of Great Wamesa Clan in Teluk Wondama West Papua: Model Pelestarian Hutan Adat Berbasis Kearifan Lokal Suku Besar Wamesa di Teluk Wondama Papua Barat - Sofwani, Ahmad; Kurube, Hendrik; Saleh, Choirul (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and describe the Indigenous Law Society (ILS) of Great Wamesa Clan in West Papua for conserved the Indigenous Forest based on the norm coventions of Siweruri Kuweta. This research is motivated by the existence of massive deforestation and forest degradation which has a serious impact on infrastructure and forest ecosystems in Indonesia. Thus placing Indonesia in unsustainable forest management, and is considered a crime against with nature. Currently, West Papua still has a sustainable forest of 81%, has a wealth of various wildlife species and various types of ecosystems (mega-Biodiversity). Therefore, the Papua Barat Government was trying to suppress the rate of deforestation with a forest development pattern based on local wisdom. This study uses qualitative methods, the data in the study are in the form of; primary and secondary data obtained from exploration results in the field through in-depth interviews, observations, and documentations which are then analyzed and concluded, resulting in empirical findings that can be used as theoretical studies, and Applicable recommendations in the context of sustainable forestry development. The results shows that ILS has consistently and continuously conserved for the Indigenous forest wisely based on the norms and traditions of Siweruri Kuweta. So that the resources and ecosystem of the Indigenous forest are maintained in balance. This condition is supported by government policies in the form of laws and regulations that are ideal in supporting the existence of ILS. As well as the implementation of a CSR (corporate social responsibility) program in an effort to improve the quality of human resources and the welfare of ILS. The researcher concludes that through the support of government policies, as well as the implementation of CSR programs can support the existence of ILS as a social buffer in the effort of sustainable forest conservation.